Simplified Internal Audits of the Welfare Quality Protocol in Dairy Farms: Are They Effective in Improving Welfare Practices? - Maria Francisca Ferreira; Catarina Stilwell; George Stilwell (Animals)
The Welfair® certificate has become an important part of food chain integrity for animal welfare assessment in several countries, relying on a rigorous audit that verifies compliance with legislation and assesses animal welfare through the Welfare Quality Protocol (WQP). Dairy cattle farmers are encouraged to conduct internal audits beforehand to self-assess the farm’s animal welfare level. Since early 2023, the Welfair® scheme has proposed simplified audits to shorten the time needed for internal audits. Ten measures are selected from the WQP, five of which must always be assessed: body condition, water provision, lameness, integument alterations, and pain management in disbudding. The main objective of this study was to determine whether analyzing the results of these five key indicators helps in identifying welfare problems, ultimately leading to a better final score. To test this, seven Portuguese commercial dairy farms were randomly selected to conduct a simplified internal audit followed by a certification audit. Considering the circumstances of our study, the visits proved essential to promoting better welfare practices, which positively influenced the final classification. However, areas that require improvement (such as the lack of an accurate risk analysis of the simplified audits provided by the Welfair® scheme) were identified and are discussed.